Strategi Optimalisasi Pembiayaan Mudharabah Pada Bank Syariah - Gurhanawan, Gurhanawan (Indonesian Center for Religion and Society Studies (InTReSt), 2020)
Islamic banks provide mudharabah financing to foster the business. This service is offered to various scale of business, encompassing smaller or larger ones. However, the amount of mudaraba financing is less prevalent than the murabaha financing, in which the latter aimed for consumptive purpose. This paper aims to determine the constraints of Islamic banks in promoting mudarabah and optimizing it as one of the means to proliferate individual financial independence through owning a business. The study uses a field research which is descriptive qualitative in nature. The findings are corroborated using SWOT analysis to discover internal and external factors related to Mudharabah. Primary data are obtained interviews with related parties in Islamic banks. Secondary data is also utilized and obtained through literature studies. The results show that the strategy established by Islamic banks in optimizing mudharabah financing by implementing the linkage program. Islamic banks cooperate with BPRS and Cooperatives using mudharabah contracts, then BPRS and Cooperatives distribute the fund to the public in, improving the economc activities.